Analisis Efektivitas Model Perkuatan dengan Injeksi Semen untuk Peningkatan Angka Keamanan Lereng - Sumirin, Sumirin; Arief, Rifqi Brilyanto (Department of Civil Engineering, Diponegoro University, 2017)
The problem of slope stability can be overcome by grouting of cement paste. But, the question often arises as to the extent of grouting of cement paste can increase the factor of safety. This study aims to determine the effectiveness of the effect of grouting on increasing safety factor on the slope of embankment. Experiments have been conducted in the laboratory using 6 types of mixed samples of sand and coarse aggregate. Field testing was conducted on 1 model to determine the effectiveness of grouting. The results of the experiments show that the injection of cement paste in this study proved to be effective in strengthening the embankment with the content of coarse aggregate 60%. The increase factor of safety (FS) using grouting is from FS= 1.9 (33.3%) to FS = 2.80 (90.0%). Factors determining the effectiveness of injection are: (a) injection method with drilling technique before injection to form cement column; (b) the optimum of water-cement ratio w/c = 1.5; (c) the ratio of spacing and injection diameter Lg / Dg = 8, the depth of injection 0.75 from the height of the embankment.